Influence of access to finance on the competitive growth of SMEs in Lesotho - Donald O. E. Amadasun; Ashley T. Mutezo (Journal of Innovation and Entrepreneurship, 2022)
Access to finance has been identified as one of the biggest problems faced by small and medium-sized enterprises (SMEs) in most developing economies. Similarly, access to finance has been identified as a dominant constraint facing the SME sector in Lesotho. This paper established the factors related to access to finance that influence the competitive growth of the SME sector in Lesotho. The factors that were identified include financial information access, bank and business support services, the structure of banks, and the collateral requirements of the financial sector.
Keywords: 650; Bank and business support services; Collateral requirement; Competitive growth; Financial information access; Small and medium-sized enterprises; Structure of the bank